Exploratory factorial structure of subjective well-being. (2019)
The quality of life has been a process highly studied from a psychological approach. In this sense, the present work was proposed to establish an explanatory model of life satisfaction to discuss the importance of other disciplines in the research of resources that satisfy individuals. Once the relationships between the factors derived from the theoretical framework and literature review were explained, it was conducted a cross - sectional study with a non - probabilistic sample of 245 students. Once established the validity and reliability of the instrument that measured life satisfaction, expected capabilities, expectations of opportunity, trust relationships, perception of justice, environmental assessment, standards context and perceived resources. From a structural model, the perceived availability of resources indirectly determined life satisfaction through standards context. The results were compared with the findings reported in the state of knowledge and brandished discussed from theoretical frameworks.